2016
DOI: 10.1021/acschembio.6b00759
|View full text |Cite
|
Sign up to set email alerts
|

Domain Organization and Active Site Architecture of a Polyketide Synthase C-methyltransferase

Abstract: Polyketide metabolites produced by modular type I polyketide synthases (PKS) acquire their chemical diversity through the variety of catalytic domains within modules of the pathway. Methyltransferases are among the least characterized of the catalytic domains common to PKS systems. We determined the domain boundaries and characterized the activity of a PKS C-methyltransferase (C-MT) from the curacin A biosynthetic pathway. The C-MT catalyzes S-adenosylmethionine-dependent methyl transfer to the α-position of β… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(87 citation statements)
references
References 49 publications
3
82
0
2
Order By: Relevance
“…In connection with these considerations, while this manuscript was under review, a structure of an excised CMeT from a modular PKS was determined and closely agrees with the present data on a comparable domain from an iterative PKS (Skiba et al, 2016). …”
Section: Discussionsupporting
confidence: 78%
“…In connection with these considerations, while this manuscript was under review, a structure of an excised CMeT from a modular PKS was determined and closely agrees with the present data on a comparable domain from an iterative PKS (Skiba et al, 2016). …”
Section: Discussionsupporting
confidence: 78%
“…Of the several hundred MT structures in the structure database, AprA MT1 most closely resembles the MTs from PKS extension steps 28, 29 . All class I SAM-dependent MTs are thought to have a common ancestor, but the superfamily has several highly diverged branches.…”
Section: Resultsmentioning
confidence: 99%
“…The lid domains are topologically similar at the N-termini, but the AprA MT1 lid (formerly known as AR) is much larger due to a C-terminal extension. We previously showed that conserved His and Glu amino acids are essential to methyl transfer by the CurJ extension-module MT, and proposed that the His imidazole is the catalytic base that accepts a proton from the α-carbon of the β-ketoacyl-ACP substrate 28 . By structure superposition, the critical His and Glu of extension-module MTs correspond to AprA MT1 His369 and Glu431, which are also conserved in GNAT loading modules (Supplementary Figure 4d, 4e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a number of excised PKS C -methyltranferases have been expressed as recombinant proteins and shown to catalyze the expected SAM-dependent methylation of 3-ketoacylthioesters, the stereochemistry of the resulting 2-methyl-3-ketoacyl thioester products has not been determined. 8,9 …”
mentioning
confidence: 99%